Developing Students’ Reading Culture for Academic Reading Level through Metacognitive Strategies - pranowo, Pranowo (Lingua Cultura, 2018)
The development of reading culture for this academic level used the metacognitive strategies. This research was a case studyÂ in wihich the data sources were randomly drawn from various print sources by cutting off the core of the text to be analyzed.Â The technique of data analysis was done with two steps. The first step was to identify each data based on the categories thatÂ contained in the cognitive domain. The second step was the results of the analysis of the cognitive domains viewed basedÂ on the metacognitive strategies that included the process of planning, monitoring, and evaluate. The results of the researchÂ are that reading culture at the academic level can be developed through metacognition strategy. The steps that can be doneÂ are the reader performs cognitive process starting from remembering, understanding, applying, analyzing, evaluating, andÂ creating. Then, every cognitive process is reviewed that the Academic reading culture can be developed with metacognitiveÂ strategies that are the type of intensive reading includes, reading comprehension, reading critically, reading creatively,Â reading interpretative, and reading reflective.